Reforma constitucional de los requisitos para postular al Congreso de la República del Perú - Lema Domínguez, Antonio Fidel (2020)
The present research work is titled “ CONSTITUTIONAL REFORM OF THE RE QUIREMENTS TO APPLY TO THE CONGRESS OF THE REPUBLIC OF PERU “said research postulates the position ofñthe need for a prior skills for the Congress of the Republic before exercising its legislative work, such training would be through a Public Institution that will seek ongoing training, updating as well as the certification and accreditation ofñthe elected congressmen and the candidates for said position. For this, this work is formed by theories related to the topic such as the Classical theory ofñLegislative Power, the Theory on Economic Voting, Weighting, Serving Law and Comparative Law. Likewise, interviews will be applied to specialists in Constitutional Law, Sociologists, Public in General and Congressmen and / or Advisors from whom the discussion ofñresults has been obtained in which the position ofñour Research is strength ened. Finally, we have the conclusions that we will reach at the end ofñthe research